2009
DOI: 10.1002/jmri.21817
|View full text |Cite
|
Sign up to set email alerts
|

A diffusion tensor imaging group study of the spinal cord in multiple sclerosis patients with and without T2 spinal cord lesions

Abstract: Purpose: To examine the T 2 -normal appearing spinal cord of patients with multiple sclerosis (MS) using diffusion tensor imaging. Materials and Methods:Diffusion tensor images of the spinal cord were acquired from 21 healthy subjects, 11 MS patients with spinal cord lesions, and 10 MS patients without spinal cord lesions on the T 2 -weighted MR images. Different diffusion measures were evaluated using both a region of interest (ROI) -based and a diffusion tensor tractography-based segmentation approach.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 52 publications
4
43
0
2
Order By: Relevance
“…[1][2][3][4][5] Interest in spinal cord DWI is increasing, however, because it is expected to be useful in a diverse range of pathology, including demyelinating disease, [6][7][8][9] infarction, 10-15 myelopathy, [16][17][18][19] and traumatic injury. [20][21][22][23] Furthermore, diffusion images serve as the raw data for DTI, 9,19,[23][24][25][26][27][28][29] which enables the mapping of white matter tracts; this could improve clinical management of pathologies such as neoplasms and spinal cord injury.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Interest in spinal cord DWI is increasing, however, because it is expected to be useful in a diverse range of pathology, including demyelinating disease, [6][7][8][9] infarction, 10-15 myelopathy, [16][17][18][19] and traumatic injury. [20][21][22][23] Furthermore, diffusion images serve as the raw data for DTI, 9,19,[23][24][25][26][27][28][29] which enables the mapping of white matter tracts; this could improve clinical management of pathologies such as neoplasms and spinal cord injury.…”
mentioning
confidence: 99%
“…Not surprisingly, a number of authors have found DTI changes in the NASC in patients with MS ( Fig. 45.2) [7,17]. A review of the literature demonstrates fairly good concordance when comparing the FA in the spinal cord in MS patients compared with controls.…”
Section: Dti In Multiple Sclerosis Of the Spinal Cordmentioning
confidence: 83%
“…9 We observed lower FA and higher MD values in patients with chronic myelitis, as previously reported. 30 Decrease in the FA values may reflect the degree of microstructural disorganization of the spinal cord, suggesting either local extracellular edema or a smaller number of fibers matching a larger extracellular space or both. 9 In addition, radial diffusivity may serve as a marker of overall tissue integrity within chronic MS lesions.…”
Section: Discussionmentioning
confidence: 99%